Barriers to firm service innovativeness in emerging economies - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2018)
Purpose This paper investigates internal and external barriers influencing the different dimensions of firm service innovativeness and the moderating effect of transformational leadership on these relationships in an emerging economy, namely, Turkey. Design/methodology/approach The hypotheses were tested using cross-sectional survey data from 148 hotels. The authors use regressions to analyze the data set. Findings The results demonstrate that barriers to innovation need not necessarily impede firm service innovativeness at all times; some of these so-called barriers may even act as catalysts that improve firm's likelihood of adopting innovations. More importantly, the findings suggest that a transformational leadership style alleviates the negative influence of internal barriers on internal service innovativeness dimensions of process, strategic and behavioral innovativeness. Originality/value The positive effect of transformational leadership lessening the detrimental impact of barriers to innovation is a topic in need of research. In addition to examining this phenomenon in a developing country, the authors choose a service retailing industry as a study context: hospitality/tourism. The main reason for choosing this industry is that there is little empirical evidence of service innovation activity in this industry despite the fact that it contributes to a large extent to employment and gross domestic product in most emerging economies, and it is, in fact, a fairly innovative industry. Furthermore, this study presents a unique perspective by investigating small- and medium-sized enterprises (SMEs).
Keywords: Emerging economy; Transformational leadership; Hospitality; Innovativeness; Barriers to innovation; TRANSFORMATIONAL LEADERSHIP; TRANSACTIONAL LEADERSHIP; PRODUCT INNOVATIVENESS; CONSUMER INNOVATIVENESS; STRATEGIC INNOVATION; OVERCOMING BARRIERS; FINANCIAL SERVICES; CONTEXTUAL FACTORS; ORIENTATION; PERFORMANCE